The effectiveness of the implementation of diversion on children who conflict with the law at the level of the state court in gorontalo province - Muhammad Rizal Lampatta; Herlina Sulaiman (Jurnal Hukum Volkgeist, 2020)
Diversion is a step or legal remedy aimed specifically at children who are in conflict with the law. As perpetrators of criminal acts, children need to be treated differently from adults. This is due to the psychological condition of children who are considered unable to accept criminal sanctions. Even children who have committed criminal acts, Act No. 11 of 2012 on the Criminal Justice System Children continue to provide collateral in the form of diversion efforts so that children avoid criminal prosecution. Diversion is carried out at the police, attorney and court levels. Not all cases of child offenders who enter the PN level can be diversified because there are already rules in the SPPA Law, Perma No. 4 of 2014 and PP. 65 of 2015. Likewise in the implementation of diversion at the District Court level in Gorontalo Province, some were successful and some were not. This study aims to determine the effectiveness of the implementation of diversion to child offenders at court level in Gorontalo Province. As well as to find out the obstacles in the implementation of diversion against child offenders at the District Court level in Gorontalo Province.